Orographical influence on the air flow over Brahmaputra Valley - MUKHERJEE, A. K.; GHOSH, S. K. (MAUSAM, 1965)
Airflow over Assam during different seasons has been examined, It has been shown that except during the monsoon, easterly air at the lower levels originates from the Himalayas. These are more marked during winter. Similarly it has been shown that there is a tendency for air to flow towards Himalayas during monsoon, Basing on this tendency the distribution of fog in winter over the whole valley has been explained. The effect of this air on the- formation of thunderstorm activity over Brahmaputra valley has also been indicated.